Carbon‐Double‐Bond‐Free Printed Solar Cells from TiO2/CH3NH3PbI3/CuSCN/Au: Structural Control and Photoaging Effects. Issue 6 (13th March 2014) - Ito, Seigo; Tanaka, Soichiro; Vahlman, Henri; Nishino, Hitoshi; Manabe, Kyohei; Lund, Peter
Abstract Carbon double bond‐free printed solar cells have been fabricated with the structure <F‐doped SnO2 (FTO)/dense TiO2/nanocrystalline TiO2/CH3NH3PbI3/Au> and <FTO/dense TiO2/nanocrystalline TiO2/CH3NH3PbI3/CuSCN/Au>, in which CuSCN acts as a hole conductor. The thickness of the CH3NH3PbI3 layer is controlled by a hot air flow during spin coating. The best conversion efficiency (4.86 %) is obtained with <FTO/dense TiO2/nanocrystalline TiO2/thin CH3NH3PbI3 (hot‐air dried)/CuSCN/Au>. However, a thick CH3NH3PbI3 layer on CuSCN is better for light‐exposure stability (100 mW cm−2 AM 1.5) when not encapsulated. Without the CuSCN coverage, the black CH3NH3PbI3 crystal changes to yellow during the light‐exposure stability test, which is due to the transformation of the CH3NH3PbI3 perovskite crystal into hexagonal PbI2.